Evaluating the impact of institutional factors and stakeholder capabilities on performance of decentralized water resources management regimes in Mozambique : the case of Limpopo river basin - Mungatana, Eric D. (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2012.